The impact of Asian financial crisis and global ICT sectors correction on the relationships between stock prices and exchange rates in ASEAN-5 - Ooi, Ai Yee; Tan, Bee Ling; Lee, Hock Ann (2005)
This paper has investigated the dynamic impacts of the Asian financial crisis and global Information, Communication and Technology (ICT) sector correction on the relationships between exchange rates and stock prices for the ASEAN-5 funding countries. They are Malaysia, Singapore, Thailand, the Philippines, and Indonesia. Using daily data 1995 – 2001, the results of variance decompositions analysis suggest that during pre-crisis, crisis and ICT bubble, the exchange rates have more influential power in influencing stock prices. Thus, this finding is in line with the traditional approach of stock prices determination, where exchange rate change is expected to give rise to stock price change. However, during post-bubble period stock prices become the dominant explanatory variable in all countries.